PETA PEMAHAMAN ILMU USHULUL FIQH JALALUDDIN AS-SUYUTHI DALAM KITAB AL-ASYBAH WA AN-NADHAIR - Hilyati Aulia; Indarwanto, Wijay Wasari (Academic Journal of Islamic Principles and Philosophy, 2023)
The science of ushul fiqh occupies a very important position in the science of Sharia because it has a very large role in takhrij al-ahkam al-islamiyyah. The science of ushul fiqh stood as an established scientific discipline in the hands of Imam Syafi’i. He made the science of ushul fiqh interesting to study or carry out a multidisciplinary approach. To understand the scientific framework of ushul fiqh, the author will formulate a map of understanding the science of ushul fiqh Jalaluddin as-Suyuthi in his work al-Asybah wa an-Nadhair. This article aims to find out the map of understanding the science of ushulul fiqh Jalaluddin as-Suyuthi in the book al-Asybah wa an-Nadhair from the aspect of the object of knowledge, the process of obtaining knowledge, and the benefits of knowledge. This article is qualitative library research using a philosophy of science approach from ontology, epistemology, and axiology. The subjects of this study were Imam Jalaluddin as-Suyuthi and the book al-Asybah wa an-Nadhair. Data will be collected using documentation techniques. The results of this study are from the ontology aspect, the main object of the study includes dalil, istidlal, and mustadil, while one follow-up object is the mass object (masail). From the aspect of epistemology, the process of knowing Imam as-Suyuthi regarding objects in the book al-Asybah wa an-Nadhair goes through three coherent stages, these stages are the heuristic stage, the critical stage, and the explanation stage. From an axiological aspect, this book deserves to be one of the main references in the science of ushul fiqh of the Shafi'i school, both for beginners and experts.